Shear Strength Characteristics of Soft Soil in Nansha District of Guangzhou - WANG Wei-qi, LIAN Chang-jiang, LI Jian-ping, CHEN Zhi-yong, CHENG Dong-hai, CAI Wei-long, TANG Kai, LI Chao (长江科学院院报, 2025)
[Objective] Shear strength serves as a key parameter in soft soil engineering, and accurately obtaining shear strength can greatly optimize project design and enhance construction safety. To investigate the shear strength characteristics of soft soils in the Nansha District of Guangzhou, geotechnical investigation data are collected from dozens of on-site survey projects. The data include both linear projects like rail transit systems and planar projects such as civil construction sites. [Methods] The collected data were statistically analyzed according to burial depths of 0-10, 10-20, and 20-30 m to obtain the quick shear strength parameters of silt and silty soil. Linear regression was performed on in-situ vane shear test results to determine the consolidated quick shear strength parameters. Triaxial compression tests were conducted on local soft soils to obtain consolidated undrained and consolidated drained strength parameters. The undrained shear strength was obtained through unconfined compressive strength tests and vane shear tests. Correlation analysis was conducted between the quick shear and consolidated quick shear strength parameters from direct shear tests. Additionally, comparative analysis was performed on the unconsolidated undrained, consolidated undrained, and consolidated drained shear strength from triaxial compression tests. Sensitivity analysis was applied to the unconfined compressive strength and vane shear test results to estimate the shear strength of remolded soil. [Results] (1) The thickness of soft soil in the study area mainly ranged from 5 to 25 m, with coastal regions in the southwestern part of Nansha District exhibiting thicknesses exceeding 45 m. (2) The quick shear strength parameters of the local soft soil were determined as follows. For silt at 0-10 m depth, the cohesion cq and internal friction angle φq were measured at 6.40 kPa and 4.10°, respectively, while those at 10-20 m depth were 8.50 kPa and 6.10°. For silty soil, the corresponding values were found to be 7.60 kPa and 5.10° at 0-10 m depth, and 8.60 kPa and 6.30° at 10-20 m depth. (3) The consolidated quick shear strength ccq of soft soil at 0-10 m depth ranged from 11.06 to 11.98 kPa, with an internal friction angle φcq varying between 2.40° and 3.11°. At 10-20 m depth, ccq exhibited a range of 5.56-13.70 kPa, while φcq ranged from 1.25°-4.76°. (4) In triaxial tests, the consolidated drained shear strength parameters (c', φ') of soft soil were determined as 13.75 kPa and 14.76°, respectively, while the consolidated undrained strengths (ccu, φcu) were 13.13 kPa and 11.50°, respectively. (5) The undrained shear strength of undisturbed soil obtained from vane shear tests and unconfined compression tests was 14.84 kPa and 15.83 kPa, respectively, indicating close agreement between the two methods. The undrained shear strength of remolded soil obtained from vane shear tests and unconfined compression tests was 4.99 kPa and 7.63 kPa, respectively. The vane shear strength of remolded soil was much lower than that from unconfined compression tests. The strength of remolded soil was approximately 1/3 to 1/2 of the strength of undisturbed soil. (6) The cohesion of soft soil under consolidated quick shear conditions increased by over 45% compared to that under unconsolidated quick shear conditions. The internal friction angle in the consolidated quick shear showed a decreasing trend compared to the unconsolidated quick shear, with most values declining by 20%-40%. Notably, at the same burial depths, the quick shear strength and consolidated quick shear strength of silty soil were greater than those of silt. (7) The cohesion values derived from triaxial unconsolidated undrained, consolidated undrained, and consolidated drained shear tests showed strong consistency. Based on the consolidated undrained shear strength, the internal friction angle of consolidated drained shear increased by approximately 30%. (8) Unconfined compression tests revealed that the sensitivity of soft soil mainly ranged from 1.4 to 3.0, while vane shear tests indicated a sensitivity range mainly from 2.0 to 4.2. Both sets of data indicate medium sensitivity. Sensitivity increased with depth initially, but began to decrease beyond a certain depth. [Conclusion] These findings provide valuable insights for soft soil engineering in the region and offer practical references for geotechnical investigation, design, and construction. Certain anomalies and unconventional patterns are observed in the dataset, including the opposite variation trends in the consolidated quick shear strength of both silt and silty soil with increasing depth, as well as the difference in the rate of strength change for silt at depths of 10 m≤h<20 m under consolidated quick shear compared to direct shear conditions. Future research should focus on collecting additional soft soil test samples to obtain more definitive conclusions.